2022
DOI: 10.1073/pnas.2122105119
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided engineering of tick evasins for targeting chemokines in inflammatory diseases

Abstract: As natural chemokine inhibitors, evasin proteins produced in tick saliva are potential therapeutic agents for numerous inflammatory diseases. Engineering evasins to block the desired chemokines and avoid off-target side effects requires structural understanding of their target selectivity. Structures of the class A evasin EVA-P974 bound to human CC chemokine ligands 7 and 17 (CCL7 and CCL17) and to a CCL8-CCL7 chimera reveal that the specificity of class A evasins for chemokines of the CC subfamily is defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…We compared the chemokine-binding selectivity of EVA-R to those of three other well-characterized class A evasins. EVA-1 has been reported to bind to only three of 24 CC chemokines tested, whereas EVA-4 and EVA-P974 (referred to hereafter as EVA-P) have been reported to bind to 17 and 14 CC chemokines, respectively ( 16 , 18 , 22 ). We expressed these evasins using HEK293 cells, purified them, and verified their chemokine binding selectivity using SPR ( Table 2 , Figs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We compared the chemokine-binding selectivity of EVA-R to those of three other well-characterized class A evasins. EVA-1 has been reported to bind to only three of 24 CC chemokines tested, whereas EVA-4 and EVA-P974 (referred to hereafter as EVA-P) have been reported to bind to 17 and 14 CC chemokines, respectively ( 16 , 18 , 22 ). We expressed these evasins using HEK293 cells, purified them, and verified their chemokine binding selectivity using SPR ( Table 2 , Figs.…”
Section: Resultsmentioning
confidence: 99%
“…S2 ), but unlikely to influence chemokine binding ( 13 , 15 , 24 ). Previous studies have shown that residues within the N-terminal regions (before the first conserved Cys residue) of EVA-1 and EVA-P play roles in chemokine binding ( 16 , 18 ). The N-terminal regions of all four evasins in the present study contain one or two predicted tyrosine sulfation sites.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations